The Blackwell Companion to the Bible and Culture. - Sawyer, John (John Wiley & Sons, 2007)
Offers a reference source about twenty-first century approaches to the Bible. Drawing on interdisciplinary and international examples, this volume explores how the Bible has impacted on all the major social contexts where it has been influential - ancient, medieval and modern, world-wide.